A novel heterogeneous catalyst NH2-MIL-88/PMo10V2 for the photocatalytic activity enhancement of benzene hydroxylation. Issue 19 (24th August 2021) - Xu, PanPan; Zhang, Liuxue; Jia, Xu; Wen, Hao; Wang, Xiulian; Yang, Suqing; Hui, Juxian
Abstract : In this work, heterogeneous catalyst NH2 -MIL-88/PMo10 V2 -3 has shown the high hydroxylation activity of benzene under visible light (a 5 W LED), which mainly attributed to the production of hydroxyl radical(˙OH) and V 5+ /V 4+ redox pair in the existence of electron (e − ). Abstract : Compared to the current commercial three-step production process involving low phenol yield, low atomic efficiency, and the formation of explosive intermediates, the direct oxidation of aromatic hydrocarbon to more desirable and important chemical industry intermediate such as phenol offers a more attractive and challenging pathway. Here, we report the selective photocatalytic hydroxylation of benzene to phenol using NH2 -MIL-88/PMo10 V2 -3 as the catalyst and H2 O2 as a mild oxidant. Heteropoly acid (PMo10 V2 ) was immobilized to metal–organic frameworks (NH2 -MIL-88), where PA anions play an essential role in anchoring NH 3+ cations to form stable heterogeneous photocatalysts. The reaction offered a high selectivity of 99% with a yield of 24% for phenol under optimum reaction conditions. Comprehensive characterizations and experiments disclosed a multistep reaction mechanism in which high dispersion of PMo10 V2, the production of hydroxyl radical(˙OH) and the formation of V 5+ /V 4+ redox pairs are responsible for the activity of the reaction in the presence of electrons (e − ). The recycling experiments were essential in confirming the reusability of the catalyst, and FT-IR characterization analysis also proved the integrity of NH2 -MIL-88/PMo10 V2 -3 after three cycles. This work provides potential applications in the green and highly efficient photocatalytic synthesis of other organic compounds and other environmental applications.